Quantitative analysis of the effect of deformation temperature on microstructure evolution and mechanical property of isothermally forged BT25y titanium alloy. (2017) - Yang, Xuemei; Guo, Hongzhen; Zhao, Zhanglong; Ning, Yongquan; Yuan, Shichong; Xin, Shewei
Abstract: In order to confirm the optimal isothermal forging process for BT25y titanium alloy, the effect of deformation temperature ranging from 880 ℃ to 1005 ℃ on the microstructures and mechanical properties was studied. Quantitative relationships between microstructure characteristics and mechanical properties were obtained. The deformation mechanisms were researched by the analysis of dislocation morphologies. Result shows that with elevated deformation temperature, the microstructure varies from equiaxed structure to bimodal structure, then basket-weave structure, and finally Widmanstatten structure. Grain boundary α layer forms and secondary lamellar α coarsens gradually when deformed above 960 ℃. As the forging temperature increases, the tensile strength shows a trend of first decrease and then rise, the elongation and reduction of area present an opposite tendency. Fracture mechanism changes from dominated ductile fracture to completely brittle cleavage fracture. The fracture toughness is well improved after β-forging. The microstructure can achieve favorable thermal stability while deformed at the temperatures of 940 ℃ and 960 ℃.